Pemanfaatan Lumpur Lapindo sebagai Sumber Silika Magnetik untuk Adsorpsi Tumpahan Crude Palm Oil - Zuhara, Wihda; Nuryanto, Rahmad; Lusiana, Retno Ariadi; Efiyanti, Lisna (Jurnal Riset Kimia, 2024)
In this paper, synthesis of silica magnetite adsorbent has been carried out from Lapindo Mud silica and magnetite (Fe3O4) using the template Cetyltrimethylammonium bromide (CTAB) through a microemulsion process. This research aims to determine the adsorption ability of magnetic silica material as an adsorbent for Crude Palm Oil (CPO) with varying contact times of 10, 20, 30, 60, 90 minutes and an adsorbate concentration of 0,2, 0,4, 0,6, 0,8 and 1 gram. Silica is obtained from Lapindo Mud extraction using the acid leaching method using HCl. Magnetite was prepared by mixing ferric chloride and ferrous chloride salts with an alkaline base. Synthesis of magnetic silica adsorbent using CTAB and 1-butanol as a surfactant and co-surfactant, respectively. The characterization results from FTIR and SEM-EDX data identified the presence of silanol (Si-OH) and Fe-O groups, magnetic silica adsorbent showed an irregular morphological pattern, the size tended to be heterogeneous, contained Fe, O and Si elements. The XRD results show that there are peaks in the (200), (311) and (440) planes, the GSA results show that the pore surface area is 37.048 m2/g, the total pore volume is 0.321 cm3/g and the pore diameter is 33.907 nm, which indicates that the pores have a mesoporous structure. Based on this research, the optimum contact time is 60 minutes with adsorption kinetics following the pseudo-second order and Langmuir isotherm with an adsorption capacity of 1.76 mg/g.